Analyzing Poems from a Semiotic Perspective:Yeats's "Sailing to Byzantium" as an Example - Haif Abbas, Ali (Journal of College of Education, 2020)
This article mainly illustrates the term “semiotics” and its role in communication. The article also questions whether semiotics, as a theoretical and analytical framework, can be applied on literary works or not. Like many poets, William Butler Yeats uses powerful words in his works and he reflects those words in his masterpieces. Sailing to Byzantium is one example in which Yeats uses different images to express the idea or the fact of human-animal condition in which we pass through a life gyre from birth to maturity to death. The images which Yeats chose are full of meanings and different connotations. Since Iraqi EFL college students are facing difficulties in understanding and analyzing the literary works, especially the poems that they are studying in their textbooks, this article aims to enhance their critical awareness in literature through applying a semiotic approach.
Keywords: Keywords: semiotics, signifier, signified, sign, symbols, Saussure, Pierce, Yeats